Pica in Dogs: overview, owners perception and intestinal perforative obstructive cases in Ibadan, Nigeria (2016)
This study aimed at presenting an overview of pica in dogs, owners’ awareness and perception of this obsessive compulsive disorder, the gastrointestinal emergencies and associated surgical risk, with the objective of re-informing and awakening small animal veterinarians to the responsibility of disease prevention through clients’ education. Structured questionnaire was administered to dog owners in Ibadan city, Nigeria, to assess the level of their awareness and perception of pica and the health risk the habit poses to dogs. Report of cases of pica managed by the author and associated gastrointestinal surgical emergencies were presented and surgical approach to management discussed. Eighty percent (80%) of dog owners knew that eating of non-food items by dogs could be prevented. Some dog owners (55.7%) agreed that their dogs do sometimes eat non-food items. Some, (72.2%) have taken specific measures to prevent this habit in their dogs, while 66% had discussed with their veterinarian. Many (71.3%) were aware that this behaviour may be associated with deficiency of vital nutrients, while 65.2% were informed that the trait could be associated with anxiety and boredom. Many dog owners (65.3%) have successfully controlled the habit while 55.6% have made efforts at preventing their dogs from eating non-food items. As a result, many of them (59.2%) have provided their dogs with toys to play with while 59.8% constantly prevent their dogs from having access to non-food items. Veterinarians should make effort to educate owners on pica habit and the danger posed by it to pets’ health including the financial and psychological stress that pet’s ill- health could have on owners